Analisis Laporan Keuangan Dan Strategi Pengelolaan Yang Efektif Pada UMKM Telur Gulung - Nesa Mia Kaasandra; Nur Imroatus Sholikah; Annisa Trimur Fadila; Lufvi Selvia Febriabti; Eva Elysa Putri; Sri Rahayuningsih (Universitas 45 Surabaya, 2024)
Financial reports are information records of an entity that can describe the performance of UMKM in running their business in an accounting period, so that they can make business decisions for business development. According to Prastowo (2015: 3) The purpose of financial reports is to provide information regarding financial position, performance and changes in financial position for Companies (UMKM) which is useful for a large number of users in making economic decisions. This research aims to analyze the financial management strategy which includes planning for disbursement funds implemented by the Egg Roll UMKM. The type of research used is a qualitative descriptive data analysis method. The data sources used are primary data and secondary data conducted through interviews and documentation. There are various strategies implemented by egg roll UMKM so that the business they start can develop and be successful, one of which is recording all financial transactions of their business so they can see the loss/profit from the sale of egg rolls